THE OPTIMIZATION OF THE EMPOWERMENT OF ZAKAT, INFAQ, AND SADAQAH IN THE GURU NGAJI BERDAYA PROGRAM: A CASE STUDY OF LAZIS NURUL FALAH OF SURABAYA - Indri Supriani; Yendi Rio Nurrachman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Poverty is a problem that cannot yet be completely resolved, especially for Qur’an teachers in remote areas of Indonesian. Islam as rahmatan lil alamin can provide solutions to these problems by optimizing Islamic philanthropic instruments such as zakat, infaq, and sadaqah by ZIS institutions, one of which is LAZIS Nurul Falah of Surabaya in the Guru Ngaji Berdaya program. This research aims to determine the optimality of ZIS funds in the Guru Ngaji Berdaya program at LAZIS Nurul Falah of Surabaya with indicators of increasing income as a benchmark and optimization steps. The method used in this research is descriptive qualitative using interview method with two managers of LAZIS Nurul Falah of Surabaya (A1 - A2) and five Qur’an teachers (B1 - B5). The results of this research indicate that informants B1 - B5 experienced an increase in income so the empowerment of ZIS in the Guru Ngaji Berdaya program was optimal. The optimization steps that can be taken by LAZIS Nurul Falah of Surabaya in the Guru Ngaji Berdaya program are being more responsive, collaboration between LAZIS Nurul Falah branches, socialization to become expert teachers, and increasing assistance in the form of business capital.